Future species composition will affect forest water use after loss of eastern hemlock from southern Appalachian forests. Issue 4 (1st June 2013) - Brantley, Steven; Ford, Chelcy R.; Vose, James M.
Abstract : Infestation of eastern hemlock ( Tsuga canadensis (L.) Carr.) with hemlock woolly adelgid (HWA, Adelges tsugae ) has caused widespread mortality of this key canopy species throughout much of the southern Appalachian Mountains in the past decade. Because eastern hemlock is heavily concentrated in riparian habitats, maintains a dense canopy, and has an evergreen leaf habit, its loss is expected to have a major impact on forest processes, including transpiration ( E t ). Our goal was to estimate changes in stand‐level E t since HWA infestation, and predict future effects of forest regeneration on forest E t in declining eastern hemlock stands where hemlock represented 50–60% of forest basal area. We used a combination of community surveys, sap flux measurements, and empirical models relating sap flux‐scaled leaf‐level transpiration ( E L ) to climate to estimate the change in E t after hemlock mortality and forecast how forest E t will change in the future in response to eastern hemlock loss. From 2004 to 2011, eastern hemlock mortality reduced annual forest E t by 22% and reduced winter E t by 74%. As hemlock mortality increased, growth of deciduous tree species—especially sweet birch ( Betula lenta L.), red maple ( Acer rubrum L.), yellow poplar ( Liriodendron tulipifera L.), and the evergreen understory shrub rosebay rhododendron ( Rhododendron maximum L.)— also increased, and these species will probably dominate post‐hemlock riparian forests. All of these species have higher daytime E L rates than hemlock, and replacement of hemlock with species that have less conservative transpiration rates will result in rapid recovery of annual stand E t . Further, we predict that annual stand E t will eventually surpass E t levels observed before hemlock was infested with HWA. This long‐term increase in forest E t may eventually reduce stream discharge, especially during the growing season. However, the dominance of deciduous species in the canopy will result in a permanent reduction in winter E t and possible increase in winter stream discharge. The effects of hemlock die‐off and replacement with deciduous species will have a significant impact on the hydrologic flux of forest transpiration, especially in winter. These results highlight the impact that invasive species can have on landscape‐level ecosystem fluxes.